Field estimates of floc dynamics and settling velocities in a tidal creek with significant along-channel gradients in velocity and SPM. (15th October 2017) - Schwarz, C.; Cox, T.; van Engeland, T.; van Oevelen, D.; van Belzen, J.; van de Koppel, J.; Soetaert, K.; Bouma, T.J.; Meire, P.; Temmerman, S.
Abstract: A short-term intensive measurement campaign focused on flow, turbulence, suspended particle concentration, floc dynamics and settling velocities were carried out in a brackish intertidal creek draining into the main channel of the Scheldt estuary. We compare in situ estimates of settling velocities between a laser diffraction (LISST) and an acoustic Doppler technique (ADV) at 20 and 40 cm above bottom (cmab). The temporal variation in settling velocity estimated were compared over one tidal cycle, with a maximum flood velocity of 0.46 m s −1, a maximum horizontal ebb velocity of 0.35 m s −1 and a maximum water depth at high water slack of 2.41 m. Results suggest that flocculation processes play an important role in controlling sediment transport processes in the measured intertidal creek. During high-water slack, particles flocculated to sizes up to 190 μm, whereas at maximum flood and maximum ebb tidal stage floc sizes only reached up to 55 μm and 71 μm respectively. These large differences indicate that flocculation processes are mainly governed by turbulence-induced shear rate. In this study, we specifically recognize the importance of along-channel gradients that places constraints on the application of the acoustic Doppler technique due to conflicts with the underlying assumptions. Along-channel gradients were assessed by additional measurements at a second location and scaling arguments which could be used as an indication whether the Reynolds-flux method is applicable. We further show the potential impact of along-channel advection of flocs out of equilibrium with local hydrodynamics influencing overall floc sizes. Highlights: Impact of along-channel gradients on in situ settling velocity estimates. Flocculation of cohesive sediments influencing sediment transport. Along-channel gradients limit the applicability of the Reynolds-Flux method.